Minimally invasive posteromedial percutaneous plate osteosynthesis for diaphyseal tibial fractures: technique description. (October 2017) - Wajnsztejn, Andre; Pires, Robinson Esteves Santos; dos Santos, Alexandre Leme Godoy; Labronici, Pedro Jose; Fernandes, Helio Jorge Alvachian; Ferretti, Mario
Abstract: Purpose: The aim of this study was to evaluate the feasibility of performing minimally-invasive plate osteosynthesis (MIPO) in tibial fractures using two posteromedial incisions, and to measure the distance between the plate and neurovascular structures. Materials and methods: We performed nine dissections of specimens that were submitted to tibial MIPO with two posteromedial incisions. One locking compression plate (LCP) of 14 to 16 holes was inserted into the submuscular tunnel in a retrograde manner. Incisions were linked to evaluate the distance between neurovascular structures and the plate. Results: During the proximal incision, a blunt dissection between semitendinosus and medial gastrocnemius tendons, as well as their lateral shift, helped to protect the main local neurovascular structures. In its distal portion, the submuscular plate tunnel insertion and its direction to the proximal incision prevented direct contact and possible damage to neurovascular structures. Moreover, we obtained successful results from a patient submitted to this procedure. Conclusion: Posteromedial MIPO represents a safe and attractive alternative for tibial fractures, particularly if there are damaged soft tissues in the anterior and medial side, or when access to intramedullary osteosynthesis is blocked.